Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembeli Minuman Yotta di Samata Kabupaten Gowa - Mutmainnah Iin; Fathurrahman Fathurrahman; Muhammad Nasri Katman (Transformasi Manageria: Journal of Islamic Education Management, 2023)
In improving marketing and sales stategis, i tis urgently needed to influence the price and product quality. The price of a product is very significant in providing value to consumers to buy a product. Prices that match the quality of the product, consumers will be interested in buying the product because consumers are not always fixated on low prices. In the research that has been carried out on the influence of the price and quality of brand beverage products in Makassar, namely Yotta drinks, where this drink is a drink that has excelled in sales throughout South Sulawesi and has many enthusiasts. The results of the study using a quantitative descriptive type approach method with Primary and secondary data sources showed that the price had a significant influence on the decisions of Yotta drink buyers, and the quality of this product had a positive influence on the decisions of Yotta drink buyers. So the conclusion from the results of this study is that the price and quality of these products both have a positive influence on the decision to purchase Yotta drinks in Samata, Gowa Regency. Keywords: price; product quality; buyer's decision; yotta drinks